An evaluation on business model of Ten's 360 and the impact of Digital Marketing on the restaurant business of Bangladesh - Jacaria, Md. Julficar (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.